Observations and modeling of rime splintering in southern ocean cumuli - Lasher‐Trapp, Sonia (author); Scott, Emma L. (author); Järvinen, Emma (author); Schnaiter, Martin (author); Waitz, Fritz (author); DeMott, Paul J. (author); McCluskey, Christina S. (author); Hill, Thomas C. J. (author) (Journal of Geophysical Research: Atmospheres, 2021)
Recent studies have suggested a correct representation of cloud phase in the Southern Ocean region is important in climate models for an accurate representation of the energy balance. Satellite retrievals indicate many of the clouds are predominantly liquid, despite their low temperatures. However, clouds containing high numbers of ice crystals have sometimes been observed in this region and implicated the secondary ice production process called rime splintering. This study re-examines rime splintering in Southern Ocean cumuli using both a new data set and high-resolution numerical modeling. Measurements acquired during the Southern Ocean Clouds Radiation Aerosol Transport Experimental Study (SOCRATES) provide an evaluation of the amount of ice in shallow cumuli sampled over two days in this region. The measurements sometimes exhibit seven orders of magnitude or more ice particles compared to amounts expected from measurements of ice-nucleating particles (INP) on the same days. Cumuli containing multiple updrafts had the greatest tendency to contain high ice concentrations and meet the expected conditions for rime splintering. Idealized numerical modeling, constrained by the observations, suggests that the multiple updrafts produce more frozen raindrops/graupel, and allow them to travel through the rime-splintering zone over an extended period of time, increasing the number of ice particles by many orders of magnitude. The extremely low number of INP in the Southern Ocean thus appears to require special conditions like multiple updrafts to help glaciate the cumuli in this region, potentially explaining the predominance of supercooled cumuli observed there.